Acceleration or Brakes: Which Is Rational for Cell Cycle-Targeting Neuroblastoma Therapy? - Kiyohiro Ando (Biomolecules, 2021)
Unrestrained proliferation is a common feature of malignant neoplasms. Targeting the cell cycle is a therapeutic strategy to prevent unlimited cell division. Recently developed rationales for these selective inhibitors can be subdivided into two categories with antithetical functionality. One applies a “brake” to the cell cycle to halt cell proliferation, such as with inhibitors of cell cycle kinases. The other “accelerates” the cell cycle to initiate replication/mitotic catastrophe, such as with inhibitors of cell cycle checkpoint kinases. The fate of cell cycle progression or arrest is tightly regulated by the presence of tolerable or excessive DNA damage, respectively. This suggests that there is compatibility between inhibitors of DNA repair kinases, such as PARP inhibitors, and inhibitors of cell cycle checkpoint kinases. In the present review, we explore alterations to the cell cycle that are concomitant with altered DNA damage repair machinery in unfavorable neuroblastomas, with respect to their unique genomic and molecular features. We highlight the vulnerabilities of these alterations that are attributable to the features of each. Based on the assessment, we offer possible therapeutic approaches for personalized medicine, which are seemingly antithetical, but both are promising strategies for targeting the altered cell cycle in unfavorable neuroblastomas.